Subdermal Magnetic Implants: An Experimental Study. Issue 2 (17th February 2018) - Harrison, Ian; Warwick, Kevin; Ruiz, Virginie
ABSTRACT: In this paper, we consider the use of permanent implanted magnets inserted into an individual's fingers as a form of human computer interface, the magnets being excited by an external coil. Tests involving amplitude detection, amplitude discrimination, frequency discrimination, temporal discrimination, and temporal gap detection were performed on implanted subjects. As a comparison the same tests were performed on individuals who had identical magnets attached to the outside of their skin. Results indicated that much smaller stimulation currents were required to achieve a sensitivity response in the implanted subjects. It is apparent that different corpuscles are affected by complex signals at different frequencies and this has a considerable effect on the results obtained and hence on the type of stimulation that can best be applied.